Detecting Signals of Large‐Scale Climate Phenomena in Discharge and Nutrient Loads in the Mississippi‐Atchafalaya River Basin. Issue 7 (3rd April 2019) - Smits, A. P.; Ruffing, C. M.; Royer, T. V.; Appling, A. P.; Griffiths, N. A.; Bellmore, R.; Scheuerell, M. D.; Harms, T. K.; Jones, J. B.
Abstract: Agricultural runoff from the Mississippi‐Atchafalaya River Basin delivers nitrogen (N) and phosphorus (P) to the Gulf of Mexico, causing hypoxia, and climate drives interannual variation in nutrient loads. Climate phenomena such as El Niño–Southern Oscillation may influence nutrient export through effects on river flow, nutrient uptake, or biogeochemical transformation, but landscape variation at smaller spatial scales can mask climate signals in load or discharge time series within large river networks. We used multivariate autoregressive state‐space modeling to investigate climate signals in the long‐term record (1979–2014) of discharge, N, P, and SiO2 loads at three nested spatial scales within the Mississippi‐Atchafalaya River Basin. We detected significant signals of El Niño–Southern Oscillation and land‐surface temperature anomalies in N loads but not discharge, SiO2, or P, suggesting that large‐scale climate phenomena contribute to interannual variation in nutrient loads through biogeochemical mechanisms beyond simple discharge‐load relationships. Plain Language Summary: Runoff of excess nutrients from crop fertilizers applied throughout the Mississippi‐Atchafalaya River Basin, particularly nitrogen (N) and phosphorus (P), pollute freshwater and coastal ecosystems such as the Gulf of Mexico. Though agriculture is the main source, year‐to‐year variation in the size of nutrient loads is largely controlled by precipitation and river flow, which mobilize nutrients from the landscape. Additional climate variables, such as temperature, influence nutrient loads by controlling rates of nutrient uptake or transformation by plants, algae, and microbes, but these processes may be difficult to detect in a nearly continental‐scale river network with heterogeneous subbasins. We identified signals of multiple large‐scale climate phenomena in the long‐term record (1979–2014) of nutrient loads from the Mississippi River and its major tributaries. Climate effects on nutrient loads, particularly N, were different and often stronger than on river flow, indicating that long‐term patterns in nutrient loads were influenced by processes beyond simple precipitation‐driven runoff. Variable effects of climate on nutrient export present challenges for reducing nutrient loads to the Mississippi River and Gulf of Mexico. Adjustments to targeted reductions may be needed as global and regional climates change. Key Points: Significant signals of large‐scale climate phenomena appear in N loads but not discharge, SiO2, or P loads in the Mississippi River Basin at multiple spatial scales Effects of climate variables differ among nutrients (N, P, SiO2 ) and nutrient forms (nitrate, ammonium) Climate‐driven processes independent of river flow contribute to temporal variation in nutrient loads within the Mississippi River Basin